Astronomical site selection for Antarctica with astro-meteorological parameters - Erdoğan, Mehmet Akif; Aktay, Alişan; Yerli, Sinan Kaan; Kurt, Z.; Bayazit, M.; Aksaker, Nazim (Experimental Astronomy, 2024)
The primary objective of this study is to employ Multi-Criteria Decision Analysis (MCDA) and Geographical Information System (GIS) techniques to identify and assess potential sites for astronomical observations in Antarctica. Our study focuses on the development of the Suitability Index for Astronomical Sites in Antarctica (SIASA). This index is formulated by merging data from satellites and models, providing extensive temporal and spatial coverage over two decades. To assess its suitability, we employed a combination of MCDA and GIS techniques, allowing us to evaluate various data, including cloud cover (CC), precipitable water vapor (PWV) levels, elevation, atmospheric temperature and wind speed. Our analysis confirmed the exceptional characteristics of Antarctica: An average of 361 cloud-free days per year, exceptionally low PWV values (0 mm), and an average elevation of 2.300 meters. The stable atmospheric wind profile further enhances its suitability for astronomical observations. Long-term trends and correlations of the data were also studied. SIASA values identified the eastern and inner parts of the Transatlantic Mountains as highly favorable for astronomical observations, while the coastal areas were considered less suitable. The best sites cover 10% of Antarctica in all SIASA scenarios, with Dome A, Ridge A and Dome F having the highest values of all stations. These findings hold considerable importance in planning future astronomical sites on the continent.